Impaired Parenting in Primiparous Mothers: Clinical Validation through Rasch Analysis - Luis Carlos Orozco Vargas; Beatriz Villamizae Carvajal; Carolina Vargas Porras (Universidad de La Sabana, 2015)
Introduction: A valid instrument is needed to establish a nursing diagnosis of impaired parenting and to conduct interventions. Objective: The purpose of this study is to validate the nursing diagnosis of impaired parenting using Rasch analysis with primiparous mothers up to 24 years of age, during the first year of child rearing, and to compare the results of the clinical validation of that diagnosis using Rasch analysis and Fehring's method to clinically validatenursing diagnosis. Method: This was a cross-sectional study based on Rasch analysis, pursuant to Messick's construct validity guidelines. Results: Twenty-seven items representing 18 parenting-defining characteristics showed content, structural, substantive and generalized validity. Conclusion: Clinically validating nursing diagnosis using Rasch analysis makes it possible to establish dimensional diagnoses with construct validity.   DOI: 10.5294/aqui.2015.15.2.2